Assessment of heat shock proteins and endothelial dysfunction in acute pulmonary embolism - In, Erdal; Deveci, Figen; Kaman, Dilara (Lippincott Williams & Wilkins, 2016)
We determined the levels of some heat shock proteins (HSP27, HSP70, and HSP90), L-arginine, asymmetric dimethylarginine (ADMA), and symmetric dimethylarginine (SDMA) levels in patients with acute pulmonary embolism. The present case-control study comprised a healthy control group (n=57) and patients with acute pulmonary embolism (n=84). HSPs, L-arginine, ADMA, and SDMA levels were measured in all of the cases. The mean age of the control group was 56.72 +/- 8.44 years, and the mean age of the patients with acute pulmonary embolism was 60.20 +/- 16.56 years (P=0.104). Compared with controls, patients with acute pulmonary embolism had significantly higher mean serum HSP27, HSP90, and ADMA levels, whereas the mean serum L-arginine and SDMA levels were lower (P<0.001, for all parameters). In patients with acute pulmonary embolism serum HSP27, HSP70, and ADMA levels were negatively correlated with partial pressures of arterial oxygen levels (r=-0.281, P=0.01; r=-0.263, P=0.016; and r=-0.275, P=0.011, respectively) and arterial oxygen saturation (r=-0.225, P=0.039; r=-0.400, P<0.001; r=-0.299, P=0.006, respectively). The findings of the present study demonstrated that oxidative stress and endothelial damage increase in acute pulmonary embolism. Copyright (C) 2016 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: asymmetric dimethylarginine; heat shock proteins; L-arginine; oxidative stress; pulmonary embolism; symmetric dimethylarginine